New variant of the firm: A market‐like form - Kapás, Judit (Journal of Business Economics and Management, 2004)
The paper is concerned with the issue of variants within a firm, the causes of their emergence and coexistence. A particular attention is paid to the New Economy’s variant called market‐like form. It is contrasted with the M‐form firm that was dominated over the last century. Significant shift in physical technology is thought to be a major force driving the evolution process of a firm which is characterized by the emergence of new variants. The paper also analyzes how the character of the production technology determines which variant of the firm is the best suitable to a particular technology. First Published Online: 14 Oct 2010